Ultrasound-assisted extraction of Polyphenols from maritime pine residues with deep eutectic solvents - Duarte, Hugo (2022)
Deep eutectic solvents represent an important alternative in the field of green solvents due to their low volatility, non-toxicity, and low synthesis cost. In the present investigation, we propose the production of enriched polyphenolic extracts from maritime pine forest residues via an ultrasound-assisted approach. A Box–Behnken experimental design with a response surface methodology was used with six variables to be optimized: solid-to-solvent ratio, water percentage, temperature and time of extraction, amplitude, and catalyst concentration. The mixture of levulinic and formic acids achieved the highest extraction yield of polyphenols from pine needle and bark biomass. In addition, the solid-to-solvent ratio was found to be the only influential variable in the extraction (p-value: 0.0000). The optimal conditions were established as: 0.1 g of sample in 10 mL of LA:FA (70:30%, v/v) with 0% water and 0 M H2SO4 heated to 30 ◦C and extracted during 40 min with an ultrasound amplitude of 80% at 37 kHz. The bioactive properties of polyphenol-enriched extracts have been proven with significant antioxidant (45.90 ± 2.10 and 66.96 ± 2.75 mg Trolox equivalents/g dw) and antimicrobial activities. The possibility to recycle and reuse the solvent was also demonstrated; levulinic acid was successfully recovered from the extracts and reused in novel extractions on pine residues. This research shows an important alternative to obtaining polyphenolenriched extracts from forest residues that are commonly discarded without any clear application, thus opening an important window toward the valorization of such residues.